The Mastery of English Phrasal Verbs among the Students of English Education Study Program - Januarta, Belly; Indrawati, Indrawati; Ansori, Muslim (English Education Department, 2021)
The objectives of this study is to find out the mastery of English phrasal verbs in terms of their separable and inseparable types among the fifth semester students of the English education study program at State Institute of Islamic Studies SAS Bangka Belitung in the academic year of 2018/2019. The method used in this study was survey method. As many as thirty students were selected as the samples. Then the data was gathered by administering a test about phrasal verbs to the students and the researcher analyzed the results which consisted of correct answers and errors. The researcher examined the test results and found that most students made correct answers in relation to phrasal verbs with optional separation. On the other hand, the majority of errors fell under the category of phrasal verbs with obligatory separation. But, overall, the students made incorrect answers more than correct answers. By using the mean score which is 48.9 out of 100, the students can be said to have a poor level of mastery of English phrasal verbs or be classified as fail/unsatisfactory because the minimum standard of mastery is 56.